Vpliv vakuumskega merilnika na tlak in sestavo preostale atmosfere - Nemanič, Vincenc (Vakuumist, 2000)
The ultimate pressure in avacuum vessel is defined as a quotient between the total autgassing rate and pumping speed. In high vacuum and espacialli un UHV,the method for determination of outgassing rate and pumping speed becomes important since the pressure gauge may influence the result. It is well known that the hot ionization gauge may be a permanent gas source, while the processes on the cathode surface may comletely change the composition of the gas. In the paper, we show the influence of the quadrupole madd spectrometer, mounted in a well outgassed UHV vessel, upon the total pressure reading and residual gas composition. It was clearly shown that the hot cathode is the main source of gas.
Keywords: visoki vakuum; ionizacija; razplinjevanje; merilniki; tlak